Multidisciplinary Social Networks Research : Second International Conference, MISNC 2015, Matsuyama, Japan, September 1-3, 2015. Proceedings - Wang, Leon.; Uesugi, Shiro; Ting, I-Hsien.; Okuhara, Koji.; Wang, Kai.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Second International Multidisciplinary Social Networks Conference, MISNC 2015, held in Matsuyama, Japan, in September 2015. The 49 full papers presented were carefully reviewed and selected from 125 submissions. The papers deal with the following topics: multidisciplinary research on social networks; ethical issues related to SNS; information technology and social networks mining.
Multidisciplinary research on social Networks -- Ethical issues related to SNS -- Information technology and social networks mining.
Keywords: Data mining; Information storage and retrieva; Social sciences -- Data processing; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Computer Appl. in Social and Behavioral Sciences; e-Commerce/e-business.